2017
DOI: 10.1590/1807-1929/agriambi.v21n11p746-751
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical attributes and pedotransfer function for predicting water retention in management systems

Abstract: A B S T R A C TThe aims of this study were to evaluate the effects of the soil structural physical attributes on the water retention and to develop pedotransfer functions (PTFs) for the estimation of the soil water content (θ) at different matric potentials of a Dystrophic Red Latosol (Hapludox) under conventional tillage (CT) and no-tillage (NT) soil management systems. The effects of long-term CT and NT (over 25 years) management on the soil bulk density (BD), total porosity (TP), macroporosity (Ma), micropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
3
Order By: Relevance
“…They found a high correlation of microporosity with water retention, and the stepwise procedure selected microporosity as a predictor variable to estimate the retention up to 500 kPa, but not as a single predictor variable. In soils managed in conventional and no-tillage systems, Auler et al (2017) also found microporosity as a predictor variable for FC and PWP, but with a lower correlation than bulk density. These findings indicate the importance of the selection of input variables in the models, as well as that of the statistical technique used to estimate soil water retention.…”
Section: Discussionmentioning
confidence: 84%
“…They found a high correlation of microporosity with water retention, and the stepwise procedure selected microporosity as a predictor variable to estimate the retention up to 500 kPa, but not as a single predictor variable. In soils managed in conventional and no-tillage systems, Auler et al (2017) also found microporosity as a predictor variable for FC and PWP, but with a lower correlation than bulk density. These findings indicate the importance of the selection of input variables in the models, as well as that of the statistical technique used to estimate soil water retention.…”
Section: Discussionmentioning
confidence: 84%
“…A MIP está diretamente relacionada com a retenção de água no solo (AULER et al, 2017). Maiores valores de microporos somados à textura argilosa encontrada no estudo, são os principais fatores de armazenamento e disponibilidade de água para as plantas em épocas de seca ou de estresse hídrico.…”
Section: Discussionunclassified
“…A relação entre estrutura e textura do solo com a retenção de água, também foi observada por diversos autores [21,32,33] que utilizaram variáveis estruturais e texturais para geração das funções de pedotransferência, corroborando com os dados encontrados no estudo. Outros autores [6,34] utilizaram apenas de variáveis estruturais ou texturais, não em conjunto, para estimativas dos parâmetros das equações geradas. A FPT apresentadas na Tabela 8 indicam que nos tratamentos com valores significativos de Ds, Mic, Argila, pH, PT e Mac são os mais adequados para a predição do teor de água no solo em Ψm distintos.…”
Section: Funções De Pedotransferência Desenvolvidas a Partir Do Banco...unclassified